Spin-momentum locking and spin-orbit torques in magnetic nano-heterojunctions composed of Weyl semimetal WTe2 - Li, Peng; Wu, Weikang; Wen, Yan; Zhang, Chenhui; Zhang, Junwei; Zhang, Senfu; Yu, Zhiming; Yang, Shengyuan A.; Manchon, A.; Zhang, Xi-xiang (Nature communications, 2018)
Spin–orbit torque has recently been intensively investigated for the purposes of manipulating the magnetization in magnetic nano-devices and understanding fundamental physics. Therefore, the search for novel materials or material combinations that exhibit a strong enough spin-torque effect has become one of the top priorities in this field of spintronics. Weyl semimetal, a new topological material that features open Fermi arc with strong spin–orbit coupling and spin–momentum locking effect, is naturally expected to exhibit an enhanced spin-torque effect in magnetic nano-devices. Here we observe a significantly enhanced spin conductivity, which is associated with the field-like torque at low temperatures. The enhancement is obtained in the b -axis WTe 2 /Py bilayers of nano-devices but not observed in the a -axis of WTe 2 /Py nano-devices, which can be ascribed to the enhanced spin accumulation by the spin–momentum locking effect of the Fermi arcs of the Weyl semimetal WTe 2 . The Fermi arcs, topological surface states of Weyl semimetals can enable the intriguing spin control and facilitate topological spintronics. Here the authors report the spin-orbit torque at the interface of WTe 2 /Py and attribute it to the enhanced spin accumulation by the spin-momentum locking effect of the Fermi arcs of WTe 2 .